Dimensionless analysis of fluid-to-particle heat transfer coefficients - Baptista, Paulo N. (1997)
Average fluid-to-particle heat transfer coefficients were experimentally determined for spherical aluminium particles heated in car☐ymethylcellulose solutions. Two situations were considered: a still panicle immersed in a moving fluid, and a particle rotating in an otherwise stagnant fluid. Fluid flow rate, rotating particle velocity, particle diameter and fluid rheological properties were varied, covering a large range of the generalized Reynolds (0 to 801) and Prandtl (69 to 5358) numbers. Average heat transfer coefficients ranged between 56 and 2612 W/m2K. The results were compared with values predicted by published dimensionless correlations, showing that correlations based on a Fro¨szling-type equation were more adequate. It was found that the contribution due to natural convection should be considered for proper correlation of the results at low Reynolds numbers. The results also show the importance of the fluid velocity profile.